Возрастные изменения белкового состава сыворотки крови американской норки и серебристо-черной лисицы - Кушнирук, В.А.; Черкащенко, Н.И. (Вестник зоологии, 1971)
As a result of an electrophoretic investigation of blood serum proteins of Mustela vison S e h r. and silver-black fox it was established that albumin amount in Af. vison Sehr . of all age groups is high (in 3 day-old animals—27.475±0.39; in 5-day-old ones— 32.165+0.3; in adult ones — 35.6± 1.20%). Great variations in the globulin fraction content are typical of all M. vison Seh r age groups. Blood serum of 3-, 5-day and adult M. vison divided into six-seven fractions: albumins,  α1,  α2-,  α3-, β1, β2 and γ-globulins. Blood serum of 3- and 5-day old silver-black foxes divided into 5—7 fractions. The absence of γ-globulins is typical of 3-day old fox-cubs, they appear in foxes at the age of 5 days.